The impact of varying concentrations of hyaluronic acid gel on the enhancement of VEGF and angiogenesis expression - Fauzia, Malianawati; Kumala, Ega Lucida Chandra; Aufani, Maulida; Syalisha, Addini Zoya; Wahyu, Adellia; Mukhlis, Muhammad Maulana Zikrullah (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Periodontal dressings can contribute to plaque accumulation, which in turn may cause inflammation, irritation of healing tissues, bacteremia, and difficulties in eating. Advances in knowledge and technology have improved the materials used in these dressings, aiming to enhance effectiveness and minimize complications. High-molecular-weight hyaluronic acid (HMW-HA) is a promising dressing material because of its anti-inflammatory properties and its ability to promote epithelial regeneration. This study aimed to determine whether different concentrations of HMW-HA gel influence vascular endothelial growth factor (VEGF) expression and angiogenesis during gingival wound healing in white rats (Rattus norvegicus) of the Wistar strain. A total of 42 rats were divided into seven groups: a negative control group (K1), a positive control group (K2) treated with 0.2% Gengigel®, and five treatment groups (P1–P5) receiving HMW-HA gel at concentrations of 0.2%, 0.4%, 0.6%, 0.8%, and 1%, respectively. Standardized 2 mm wounds were created with a punch biopsy on the lower anterior jaw of each rat. Treatments were administered twice daily for seven days. VEGF expression and angiogenesis were evaluated using immunohistochemical and hematoxylin–eosin staining. The group treated with 1% HA gel (P5) showed the highest average VEGF expression and angiogenesis compared with the negative control and lower-concentration treatment groups. These findings suggest that topical application of HMW-HA gel may enhance gingival wound healing in periodontal surgery by promoting angiogenesis and increasing VEGF expression.